A case of pulmonary tumor thrombotic microangiopathy associated with lung cancer diagnosed by cell-block immunohistochemistry of pulmonary microvascular cytology. (2019) - Yamakawa, Hideaki; Oba, Tomohiro; Ohta, Hiroki; Tsukahara, Yuta; Kida, Gen; Tsumiyama, Emiri; Nishizawa, Tomotaka; Kawabe, Rie; Sato, Shintaro; Akasaka, Keiichi; Amano, Masako; Kuwano, Kazuyoshi; et al.
Abstract: Pulmonary tumor thrombotic microangiopathy (PTTM) is rare but should be considered as a possible diagnosis in patients with cancer. In this case, PTTM induced by lung cancer was more accurately diagnosed using cell block immunohistochemistry of pulmonary microvascular cytology (PMC) because we could confirm that lung adenocarcinoma was the origin of PTTM by the positive result of TTF-1 for atypical cells in PMC. The PMC procedure was minimally invasive and safer than lung biopsy. We believe that the cell block technique of PMC should be considered as one diagnostic option in PTTM.